Touching the future: a handbook for church-based children's leaders - Dallow, Gill (Oxford: The Bible Reading Fellowship, 2002)
This handbook aims to help anyone starting children's ministry from scratch. It includes practical suggestions for running church-based groups and is designed to help the individual reader identify key issues.
Four sections. 1. Knowing our theological roots: A theology of childhood and the biblical basis for working with children in the church today. 2. How Children Grow: Theories and aspects of child development and how to make critical use of the material. 3. Children and the worshipping community: How children develop in worship, including the place for all-age worship, spiritual gifts and sacraments. 4. How it works: Practical skills for working with children in the local church.
Keywords: Church work with children; Children -- Religious life -- Handbooks, manuals, etc; Church work with children -- Handbooks, manuals, etc